THE BEGINNING OF ISLAMIC PHILOSOPHY - Yunizar Ramadhani (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2020)
The theme presented in this article is not a new one and is fairly commonplace in countless studies of Islamic philosophy. However, the description in this article is written with a special emphasis, namely that Islamic philosophy is an attempt to explain religious teaching philosophically and that philosophy is useful for defending religious doctrines through rational-demonstrative arguments. This emphasis is present amidst the persistence of negative sentiments and even rejection raised by some Muslims, as well as criticism from philosophical reviewers who doubt the originality of religious philosophy. For this reason, the author tries to present a brief history of the emergence of Islamic philosophy along with the motives that prompted Muslim scholars to build this philosophy and the influence that surrounded it. Next, the author will explain how Muslim philosophers proved the originality of their philosophy. Everything is conveyed to state that Islamic philosophy is not as alleged by its opponents.